كتب قواعد اللغة العربية في المعاهد الإسلامية بإندونيسيا: بناؤها ونوعها ‏وعلاقتها بطرق تعليمها - Muhammad Zaenuri (LISANIA: Journal of Arabic Education and Literature, 2019)
Arabic is a foreign language for Indonesian people. Among the languages of Arabic that are widely taught in Islamic boarding schools in Indonesia are the grammar of Arabic or nahwu and sharaf. Among the elements of teaching are books, books have an important role in the learning process. This study aims to find out the Arabic grammar books used in Islamic boarding schools in Indonesia, analyze their constructs, their models and their relevance to Arabic grammar learning for non-Arabs. This research is a literature research. Data collection uses documentation techniques, while the analysis technique uses content analysis. From the results of the study, it is found that the Arabic grammar books used in Islamic boarding schools are books compiled with the qawa'id ilmiyah approach instead of qawa'id ta'limiyah, so it needs the development of methods in learning so that the students (santri) not only memorize the rules, but are also able to apply them in language skills. While in terms of the drafting model, there are at least three models, namely, matan, syarah, and khasiyah.